A case study on the "mamaratbat" its existence in the Filipino Catholic society - Echavez, Maricel Salvador (1998)
The study is about the "mamaratbat", a person who leads a prayer offered to the dead. It is participated by six subjects from within the municipality of La Paz, Leyte and twenty students of the University of the Philippines have been randomly chosen. The objective of this study is to dig up information about them, a profile on how they become on and the student's awareness of their existence and role in the Catholic society. Its discussion entails all about them and how they perceive themselves and their vocation, lending services to other people through prayers. This study is based on the assumptions that somebody who is a "mamaratbat" can be considered a "relihiyosa" or one who has a strong faith with the power of God and the power of prayers to invoke Him.